Optimization on ejector key geometries of a two-stage ejector-based multi-evaporator refrigeration system. (1st November 2018) - Yan, Jia; Wen, Na; Wang, Ling; Li, Xianbi; Liu, Zhan; Li, Shengyu
Highlights: A two-stage ejector-based multi-evaporator refrigeration system was presented. Effects of key geometries on two-stage ejector performances were investigated. Optimum values of the key geometric parameters were obtained. Abstract: A three-evaporator and dual-ejector refrigeration system was presented in this paper. By combining two single ejectors as a whole, the authors attempted to discuss the effects of key geometric dimensions of each stage on both stage performances with two-dimensional CFD simulation method. First, the CFD models were validated by experimental data. Then, the primary nozzle diameters of both stages were determined by the cooling load demands of the refrigerating and air-conditioning chambers. Next, the detailed effects of key geometric parameters such as the length of constant-pressure mixing section, the length of constant-area mixing section and area ratio of each stage on two-stage performances were identified with simulations. Finally, the optimum values of the key geometric parameters were obtained, and the results showed that the area ratio had the most significant influences on the entrainment ratio of both stages as compared to other parameters.